UNLOCKING THE POWER OF DIGITAL LEARNING: INVESTIGATING THE IMPACT OF MOBILE APPS AND SOCIAL MEDIA ON ENHANCING BIOLOGYAND SCIENCE COMMUNICATION - OGBE, Kasarachi Faustina; OKAFOR, Ifeatu Grace Ukamaka (Int’l Journal of Education Research and Scientific Development, 2024)
This study explores the potential of mobile apps and social media in enhancing biology education and science communication. It offers a comprehensive approach to understanding the role of digital technologies in improving learning outcomes, promoting science literacy, and fostering public engagement with science. The integration of mobile applications in biology education has emerged as a transformative approach to enhance student engagement, motivation, and learning outcomes.This study investigates the power of digital learning thereby investigating the impact of mobile Apps and social media role of social media in supporting biology education and science communication. A mixed-methods approach was employed, combining survey research and content analysis. The results show that social media platforms, particularly Twitter, Instagram, and Facebook, are widely used by biology educators and students to share scientific information, discuss research findings, and collaborate on projects. Social media enhances student engagement, motivation, and understanding of biological concepts.The findings suggest that mobile apps can significantly enhance biology education by catering to diverse learning needs and promoting active participation among students.